Yield and Nutrient Response of Four Popular Fertilizers applied to Kentucky Bluegrass (Poa Pratensis) - Bablitch, Michael G. (University of Wisconsin-Stevens Point, College of Natural Resources, 1981)
Three popular brand name fertilizers, Scotts, Agrico, and Milorganite, and a Urea plus Potassium Chloride mixture were applied to a Kentucky bluegrass. Fertilizers were applied at a rate of 1 pound of actual nitrogen per 1000 ft^2. Three weeks following fertilizer application, grass cuttings occurred at 3 consecutive 3-week intervals. Fertilizer response was measured by weighing grass clippings to determine yield and analyzing grass tissue to determine nitrogen, phosphorus and potassium uptake. Analysis of variance indicated no significant difference from one cutting to the next for yield, nitrogen, and phosphorus uptake. Potassium uptake did vary significantly from one period to the next. The study shows a statistically significant difference. Scotts, Agrico and Urea plus Potassium Chloride mixture were equally effective in producing yield and supplying nutrients. Milorganite, the only organic fertilizer tested, was not effective. Performance and price are the two most important factors in selecting a fertilizer. Based on these two factors, the Urea plus Potassium Chloride mixture proved to be the best buy in this study.